2009
DOI: 10.1182/blood-2009-05-222133
|View full text |Cite
|
Sign up to set email alerts
|

Cotreatment with panobinostat and JAK2 inhibitor TG101209 attenuates JAK2V617F levels and signaling and exerts synergistic cytotoxic effects against human myeloproliferative neoplastic cells

Abstract: IntroductionPhiladelphia chromosome-negative myeloproliferative neoplasms (MPNs) are a group of clonal hematopoietic disorders that includes polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). 1,2 Recent studies have confirmed the pathogenetic involvement of an acquired, somatic, gain-offunction, activating, point mutation JAK2V617F in MPNs. [3][4][5][6] This represents a guanine to thymidine mutation in exon 14 resulting in a valine to phenylalanine substitution at codon 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 51 publications
7
135
0
Order By: Relevance
“…Panobinostat has been shown to promote JAK2V617F degradation synergistically with TG101209. 91 A phase 1 study of the drug used alone in MF demonstrated clinical effects at low doses given during a long period of time with minimal adverse effects. 92 There are currently 2 phase 1/2 trials assessing the safety and tolerability of the combination of panobinostat and ruxolitinib (Table 2).…”
Section: Hdacimentioning
confidence: 99%
“…Panobinostat has been shown to promote JAK2V617F degradation synergistically with TG101209. 91 A phase 1 study of the drug used alone in MF demonstrated clinical effects at low doses given during a long period of time with minimal adverse effects. 92 There are currently 2 phase 1/2 trials assessing the safety and tolerability of the combination of panobinostat and ruxolitinib (Table 2).…”
Section: Hdacimentioning
confidence: 99%
“…29 In other words, in human MPN, especially in MF, targeting a signaling network or multiple oncogenic pathways, rather than an isolated JAK-STAT pathway, might be necessary to secure histopathologic remissions and eradication of the ancestral clone. [65][66][67] The absence of drug-induced selective clonal suppression is not a trivial shortcoming because of the implications regarding the prospect of JAK inhibitor therapy to modify disease rather than simply palliate symptoms. Current information from ruxolitinib clinical trials suggests a mechanism of action that includes a nonspecific myelosuppressive effect (possibly responsible for its salutary effect on leukocytosis, thrombocytosis, and splenomegaly and its side effects of anemia and thrombocytopenia) and an anti-JAK-STAT-mediated down-regulation of inflammatory cytokine activity (possibly responsible for its palliative effect on constitutional symptoms and cachexia; Figure 1).…”
Section: Mechanism Of Action: Do We Know?mentioning
confidence: 99%
“…32 Other HDAC inhibitors, including ITF2357 (givinostat) and panobinostat, also showed potent antiproliferative and proapoptotic activity against murine and human cells expressing JAK2V617F. 24,33 Therefore, inhibition of HDAC could be useful in treating MPNs. In the present study, we tested the efficacy of vorinostat in an animal model of Jak2V617F ϩ MPN.…”
Section: Introductionmentioning
confidence: 99%